Undertaking procedure an alternative way to sttele disputes before the competition council - Nemouchi, Habiba; Allouache, Mehdi (Journal of Human Sciences, 2023)
The legislator has provided the Competition Council with a set of legal procedures, and various tools and repressive mechanisms to carry out its role of protecting competition against practices that violate it. and In order to avoid conflicts between the offending company and the Competition Council, and to speed up the study of cases, the legislator has authorized alternative procedures for the settlement of disputes by the Competition Council, which are the procedures negotiation as resulting in a consensual agreement that puts an end to the dispute between the Competition Council and the offending company. In Algeria, the legislator has adopted the Undertaking procedure as one of the alternative aspects To settle the disputes of the Competition Council through article 60 of the competition law.